Functionalization of polymers using an atmospheric plasma jet in a fluidized bed reactor and the impact on SLM-Processes - Sachs, Marius; Schmitt, Adeliene; Schmidt, Jochen; Peukert, Wolfgang; Wirth, Karl-Ernst (29th International Conference of the Polymer Processing Society, 2014)
In order to improve thermoplastics (e. g. Polyamide, Polypropylene and Polyethylene) for Selective Laser Beam Melting (SLM) processes a new approach to functionalize temperature sensitive polymer powders in a large scale is investigated. This is achieved by combining an atmospheric pressure plasma jet and a fluidized bed reactor. Using pressurized air as the plasma gas, radicals like OH* are created. The functionalization leads to an increase of the hydrophilicity of the treated polymer powder without changing the bulk properties. Using the polymers in a SLM process to build single layers of melted material leads to an improvement of the melted layers.
Keywords: fluidized bed reactor; atmospheric pressure plasma jet; polymer functionalization